2014
DOI: 10.37333/001c.002001004
|View full text |Cite
|
Sign up to set email alerts
|

STEM and Service-Learning: Does Service-Learning Increase STEM Literacy?

Abstract: The importance of education in science, technology, engineering, and mathematics (STEM) disciplines is again a topic of discussion among policy makers and scientists, particularly given perceived declines in STEM performance by students in the U.S. Service-learning has been used in innovative and creative ways to enhance learning in a variety of STEM-related courses. Improving STEM literacy is also a focal point of STEM education and has been explicitly linked to servicelearning projects. Herein the authors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Recommendations for future research. Early researchers called for improvements to the rigor in service-learning research (Butin, 2006;Fitch, 2007;Hayford et al, 2014). The expectations and resulting quality of SoTL and discipline-based education research has increased in recent years (Talanquer, 2014).…”
Section: Gaps In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for future research. Early researchers called for improvements to the rigor in service-learning research (Butin, 2006;Fitch, 2007;Hayford et al, 2014). The expectations and resulting quality of SoTL and discipline-based education research has increased in recent years (Talanquer, 2014).…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Many variables can influence these benefits, though, including the type of reflection used in the course and the mandatory nature of the service-learning experience (Yorio & Ye, 2012). While the research specifically within STEM courses is more limited, studies have reported positive student benefits, including enhanced science literacy (Hayford et al, 2014), improved self-efficacy (Sliker, 2020), as well as a stronger understanding of social issues and the role of science in society (Glover et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Instructors also emphasize aspects such as intensive preparation, high complexity and the balance between ensuring societal impact and learning outcomes simultaneously (Butin, 2006; Kolenko et al , 1996; Marullo et al , 2009). Even though SL is said to have immense transformational potential, to date, this potential of innovative SL formats has not been fully realized (Butin, 2005; Hayford et al , 2014; Renn et al , 2012). SL is often considered a US-American approach that has not been globally adopted.…”
Section: Theorymentioning
confidence: 99%
“…Often, science service-learning projects take the format of tutoring or performing demonstrations for youth, or biomonitoring ( 17 , 19 22 ). Service-learning has been shown to increase science, technology, engineering, and math (STEM) literacy ( 21 ) and student achievement of learning outcomes ( 18 , 20 , 23 ). Service-learning may have the potential to increase student motivation to learn biology, as found in chemistry ( 24 ), and may increase students’ abilities to apply biology to real-world situations or make connections between their service and coursework ( 17 , 25 ).…”
Section: Introductionmentioning
confidence: 99%